A novel BODIPY-based photosensitizer with pH-active singlet oxygen generation for photodynamic therapy in lysosomes. Issue 34 (14th August 2019) - Wang, Chengjun; Qian, Ying
Abstract : A photosensitizer with protonation-enhanced 1 O2 generation could undergo ISC to generate 1 O2 and target lysosomes to achieve PDT. Abstract : A novel photosensitizer BDPI-lyso has been developed for photodynamic therapy (PDT). The photosensitizer BDPI-lyso showed a high singlet oxygen quantum yield ( Φ Δ = 0.95) and low fluorescence quantum yield ( Φ F = 0.05) in EtOH. Different singlet oxygen quantum yields were found in acidic solution (pH = 5, Φ Δ = 0.51) and in neutral solution (pH = 7, Φ Δ = 0.38). DFT and TD-DFT calculations of BDPI-lyso and its protonated product BDPI-lysoH + indicated that the S1 /T3 transition was responsible for the intersystem crossing (ISC) enhancement which would promote the production of singlet oxygen. The negligible dark cytotoxicity toward the hepatoma cell line Bel-7402 was confirmed by MTT assay, AO/EB dual staining, and cell images. Upon exposure to a low dose of light illumination, the disruption of the cell plasma membrane and the calculated half-maximal inhibitory concentration (IC50 ) of 0.4 μM showed a high phototoxicity of the photosensitizer BDPI-lyso. The light-induced intracellular ROS generation was verified as the PDT mechanism of BDPI-lyso. Colocalization experiments of LysoTracker Green and BDPI-lyso in the dark indicated the good lysosome-targeting ability of BDPI-lyso. The images of cells costained with LysoTracker Green and BDPI-lyso, and the appearance of intracellular and extracellular blebs with green fluorescence after light illumination revealed the light-induced dysfunction of lysosomes and cell apoptosis.